Implementation gaps in food safety interventions: evidence from a multi-vocal review focusing on animal-source foods in Ethiopia - Bekele, Meseret; Grace, Delia; Knight-Jones, Theodore J.D.; Mutua, Florence; Lindahl, Johanna F.; Daivadanam, M. (Frontiers Media, 2025)
Background: Food safety in Sub-Saharan Africa, including Ethiopia, is shifting from identifying risks to implementing solutions, especially in the production, handling, and processing of animal-source foods. These foods are an essential and highly nutritious part of human diets in Ethiopia but pose significant health risks due to a high prevalence of foodborne illnesses which originate from consumption of infected animal products or from contamination along the value chain.Objective: This study aimed to analyze the current food safety intervention landscape in Ethiopia, to identify critical gaps and challenges related to the implementation of interventions aimed at improving the safety of animal-source foods.